Plant-based shoe (PBS) / Mohammad Fathullah Jameini and Leviana Andrew - Jameini, Mohammad Fathullah; Andrew, Leviana (2020)
Shoes do not decompose easily and among the most difficult to recycle. Shoes made from leathers and cotton that cannot be recycled and rubber that cannot be decomposed. Currently, shoes are made at least with 35% PVC and EVA can take as much as 1,000 years to decompose. Shoe wastes produce chemical toxic and lead to contamination of soil and groundwater. As shoes take a very longtime to decompose, it takes up a lot of space in landfill. Hence, the Plant-based Shoe (PbS) is designed specifically using polyesters (Polyhydroxyalkanoates or PHAs) which are produced in nature by numerous microorganisms, including through bacterial fermentation of sugars or lipid and commonly found in palm oil. PHAs are widely used in biochemical application but it also can be used to produce biodegradable plastics. Using Plant-based Shoe will help promoting environmental-friendly practices and lifestyle, reducing pollution and contamination caused by improper waste management and utilizing the abundant amount of palm oil in Malaysia. What most unique about PbS is that the material is biodegradable, free from harmful chemical and can be incorporated into any type of shoe.